2019
DOI: 10.2147/ott.s191571
|View full text |Cite
|
Sign up to set email alerts
|

<p>High Tiam1 expression predicts positive lymphatic metastasis and worse survival in patients with malignant solid tumors: a systematic review and meta-analysis</p>

Abstract: Background: Many studies have explored the prognostic value of T-cell lymphoma invasion and metastasis inducing factor 1 (Tiam1) and its association with lymphatic metastasis in malignant solid tumors, but the conclusions remain controversial. Therefore, we performed a meta-analysis to systematically assess the prognostic value of Tiam1 expression and its association with lymphatic metastasis in malignant solid tumors. Methods: We searched eligible studies in PubMed, Web of Science and EMBASE databases (from i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 71 publications
1
4
0
Order By: Relevance
“…Therefore, in PDAC, high level of RASAL2 might cause TIAM1 overexpression. Consistently, TIAM1 acts as a key gene associated with cancer malignancy [30][31][32][33][34], high TIAM1 expression was significantly related with shorter overall survival (OS) and disease-free survival (DFS) and was clearly associated with metastasis in patients with solid cancers [37,38].Our current study has for the first time shown that RASAL2 promotes PDAC malignancy by enhancing YAP1/TIAM1 signaling in PDAC. Specifically, RASAL2 promoted TIAM1 expression by upregulating YAP1.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Therefore, in PDAC, high level of RASAL2 might cause TIAM1 overexpression. Consistently, TIAM1 acts as a key gene associated with cancer malignancy [30][31][32][33][34], high TIAM1 expression was significantly related with shorter overall survival (OS) and disease-free survival (DFS) and was clearly associated with metastasis in patients with solid cancers [37,38].Our current study has for the first time shown that RASAL2 promotes PDAC malignancy by enhancing YAP1/TIAM1 signaling in PDAC. Specifically, RASAL2 promoted TIAM1 expression by upregulating YAP1.…”
Section: Discussionsupporting
confidence: 67%
“…In PDAC, high expression of TIAM1 suggested a poor prognosis and silencing TIAM1 decreased tumor cell proliferation, migration and invasion [36]. Moreover, a systematic review and meta-analysis revealed that high TIAM1 expression was significantly related with shorter overall survival (OS) and disease-free survival (DFS) and was associated with metastasis in patients with solid cancers [37,38]. PDAC expresses a high level of TIAM1 expression and predicts a poor prognosis, while mechanistically silencing TIAM1 decreases tumor cell proliferation, migration and invasion [36].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor-associated lymphatic vessels are closely correlated with metastasis and clinical outcomes in various types of cancer [ [22][23][24]. Herein, the antilymphangiogenic and antilymphatic metastatic functions of aiphanol were explored.…”
Section: Discussionmentioning
confidence: 99%
“… 71 Furthermore, 1A-116 inhibits Rac1 signalling pathway by preventing its interaction with T-lymphoma invasion and metastasis-inducing protein-1 (TIAM1), a guanine exchange factor, 61 whose high expression is associated with increased lymphatic metastasis and worse patient survival in different cancers. 72 Additionally, 1A-116 has a chronotherapeutic effect against GBM and its efficacy is regulated by the circadian clock. In a study on mouse xenografts (with GBM LN229 cells), Trebucq et al 61 reported that low concentrations of 1A-116 applied near the peak of TIAM1 expression have similar effects for its application with saturating concentrations at different time points.…”
Section: Chronotherapy Drugs/approaches In Glioblastomamentioning
confidence: 99%